Whole genome sequencing puts forward hypotheses on metastasis evolution and therapy in colorectal cancer. Issue 1 (December 2018) - Ishaque, Naveed; Abba, Mohammed; Hauser, Christine; Patil, Nitin; Paramasivam, Nagarajan; Huebschmann, Daniel; Leupold, Jörg; Balasubramanian, Gnana; Kleinheinz, Kortine; Toprak, Umut; Hutter, Barbara; Benner, Axel; et al.
Abstract Incomplete understanding of the metastatic process hinders personalized therapy. Here we report the most comprehensive whole-genome study of colorectal metastases vs. matched primary tumors. 65% of somatic mutations originate from a common progenitor, with 15% being tumor- and 19% metastasis-specific, implicating a higher mutation rate in metastases. Tumor- and metastasis-specific mutations harbor elevated levels of BRCAness. We confirm multistage progression with new componentsARHGEF7/ARHGEF33 . Recurrently mutated non-coding elements include ncRNAsRP11-594N15.3, AC010091, SNHG14, 3' UTRs ofFOXP2, DACH2, TRPM3, XKR4, ANO5, CBL, CBLB, the latter four potentially dual protagonists in metastasis and efferocytosis-/PD-L1 mediated immunosuppression. Actionable metastasis-specific lesions includeFAT1, FGF1, BRCA2, KDR, andAKT2 -, AKT3 -, andPDGFRA -3' UTRs. Metastasis specific mutations are enriched in PI3K-Akt signaling, cell adhesion, ECM and hepatic stellate activation genes, suggesting genetic programs for site-specific colonization. Our results put forward hypotheses on tumor and metastasis evolution, and evidence for metastasis-specific events relevant for personalized therapy. The evolution and genetic nature of metastatic lesions is not completely characterized. Here the authors perform a comprehensive whole-genome study of colorectal metastases in comparison to matched primary tumors and define a multistage progression model and metastasis-specific changes that, in part, are therapeutically actionable.